Living with ticks: Results of an online survey of the knowledge, attitudes and practices (KAP) regarding ticks and tick-borne pathogens in academic environments across Europe - Estrada-Peña, Agustín; Antunes, Sandra; Domingos, Ana; Esser, Helen; Földvári, Gábor; Fuehrer, Hans-Peter; Gargili, Aysen; van Gestel, Mats; Grandi, Giulio; Kazimirova, Maria; Kiewra, Dorota; Klemola, Tero; et al. (ELSEVIER GMBH, 2025)
We prepared a digital questionnaire to capture knowledge, attitudes and practices (KAP) regarding ticks and tick-borne pathogens (TBPs) in 20 languages. The questionnaire was distributed to 21 universities and research institutions in 22 European countries and 9401 valid responses were collected. Most survey participants identified ticks correctly and regarded ticks as a serious health risk. There was also a good level of knowledge regarding tick activity, habitats and the predominant TBPs in the country or region. Moreover, most respondents were familiar with effective tick protection and removal measures. Over 75 % of respondents had been bitten by ticks and up to 12 % of participants had been diagnosed with a tick-borne infection in the past. Respondents from northern and central European countries who reported engaging in outdoor activities more frequently, reported increased frequencies of tick bites and infection with TBPs compared to respondents from southern Europe. Awareness of national information campaigns on ticks and TBPs was also greater among respondents from northern and central European countries than among Mediterranean countries. This study identified knowledge gaps among respondents from some European countries where TBPs have not been prioritised historically. These knowledge gaps should be addressed by reputable bodies to encourage personal protective behaviours without causing alarm and to forestall the spreading of incorrect and unreliable information propagated by some social media sources.